2013
DOI: 10.1136/jech-2012-202027
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D3and the risk of pneumonia in an ageing general population

Abstract: These data suggest an inverse effect of serum 25(OH)D₃ concentration on the risk of incident pneumonia in the general ageing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…Third, a recent study reported that a higher BMI led to lower 25(OH)D 3 levels [40]. More recently, Aregbesola and colleagues found that subjects with a lower serum 25(OH)D 3 concentration had a higher risk of pneumonia [41]. Fourth, leptin ( ob/ob ) and leptin receptor ( db/db ) deficient mice showed severe immune abnormalities and greater susceptibility to viral and bacterial infection [42].…”
Section: Discussionmentioning
confidence: 99%
“…Third, a recent study reported that a higher BMI led to lower 25(OH)D 3 levels [40]. More recently, Aregbesola and colleagues found that subjects with a lower serum 25(OH)D 3 concentration had a higher risk of pneumonia [41]. Fourth, leptin ( ob/ob ) and leptin receptor ( db/db ) deficient mice showed severe immune abnormalities and greater susceptibility to viral and bacterial infection [42].…”
Section: Discussionmentioning
confidence: 99%
“…Two prospective studies on incidence of pneumonia among the elderly yielded information on the 25(OH)D concentration–pneumonia incidence relation—one from Finland, 57 one from the US 31 Using those values along with the 25(OH)D concentration percentiles for elderly Canadians results in a 31% reduction in pneumonia on the basis of the Finnish study and a 72% reduction on the basis of the US study. Closer to home is a study from Canada based on students at McMaster University, Hamilton, Ontario, that enrolled 600 students.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were also obtained in other studies. Aregbesola et al [57] investigated the risk of hospitalized pneumonia in an ageing general population in eastern Finland. On the basis of the study, the authors suggested an inverse effect of the serum 25(OH)D concentration on the risk of developing pneumonia.…”
Section: Vitamin D Versus Influenza—prevention or Therapy?mentioning
confidence: 99%